Tax compliance costs for policy makers: small and medium enterprise in Thailand - Chunhachatrachai, Papaporn; Pope, Jeffery (International Council for Small business, 2012)
While tax compliance costs are often neglected, the costs are important for policy-making. At present, there is no study of tax compliance costs of Small and Medium Enterprises in Thailand. The importance of tax compliance costs has not been considered with tax policy. It is timely for tax policy makers in Thailand to recognise the issue of tax compliance costs. In relation to research methodology, a survey questionnaire was designed to obtain quantitative data. In the year 2010, the tax compliance costs of SMEs were 251,100 baht and the effects to Thai SMEs were as hidden costs and a tax burden. Concerns about tax compliance costs in the tax policy area should be considered by the government in Thailand. Good tax policy should not be a burden to taxpayers, so to reduce the tax compliance costs should be a priority for tax officials if they are to support SMEs.While tax compliance costs are often neglected, the costs are important for policy-making. At present, there is no study of tax compliance costs of Small and Medium Enterprises in Thailand. The importance of tax compliance costs has not been considered with tax policy. It is timely for tax policy makers in Thailand to recognise the issue of tax compliance costs. In relation to research methodology, a survey questionnaire was designed to obtain quantitative data. In the year 2010, the tax compliance costs of SMEs were 251,100 baht and the effects to Thai SMEs were as hidden costs and a tax burden. Concerns about tax compliance costs in the tax policy area should be considered by the government in Thailand. Good tax policy should not be a burden to taxpayers, so to reduce the tax compliance costs should be a priority for tax officials if they are to support SMEs.